PUSHPAGHNI JATAHARINI IN MODERN SCIENTIFIC PERSPECTIVE: A REVIEW (AYUSHDHARA, 2018)
Jataharini has described by Acharya Kashyapa in Revati Kalpaadhyaya of Kalpasthana in Kashyapa Samhita. Jataharini is a group of disease that affects the women during their different stages of life. It not only affects the women but also their foetuses, neonates and children. Pushpaghni Jataharini is one of them which affect the women at their reproductive age. Adharma (unrighteousness) is a most important cause for affliction by Jataharini as described by Acharya Kashyapa. Adharma may be said to some extent as lifestyle changes in present time. This lifestyle changes due to modernization has given rise to many lifestyle disorders like diabetes, cardiovascular diseases and polycystic ovarian disease etc. PCOS is one of the most common lifestyle disorders occurring in females. PCOS is emerging as a burning disease affecting a growing number of urban Indian women. A recent rise in PCOS cases in urban India may be due to modernization, stress and lifestyle changes. By analyzing the symptoms of both Pushpaghini Jataharini and PCOS, it is found that both are similar to some extent. In ancient time, Acharya Kashyapa has considered spiritual power responsible for disease. The causation of disease is not defined on scientific role of Doshas. An effort is made in this article to give some scientific reasons why Pushpaghini Jataharini is close to the Polycystic Ovarian Syndrome. As India has been labelled as the ‘diabetic capital of the world’ due to an alarming increase in the number of cases of both diabetes and metabolic syndrome, it is possible that there may be an increasing number of cases of PCOS as well as because PCOS is also a disorder of insulin metabolism. Thus PCOS is a syndrome showing an alarming rise in India and adding economic health burden of the country.